Gender features of structural and functional changes of the heart and levels of copeptin and NTproBNP in patients with acute Q-myocardial infarction in the presence of pulmonary hypertension - V. D. Syvolap; Ya. V. Zemlianyi; D. A. Lashkul (Zaporožskij Medicinskij Žurnal)
The aim. To evaluate the gender features of structural and functional changes in the heart and levels of copeptin and NTproBNP in patients with acute myocardial infarction (AMI) with concomitant pulmonary hypertension (PH).